2016
DOI: 10.1111/bjet.12501
|View full text |Cite
|
Sign up to set email alerts
|

A pedagogy for outreach activities in ICT: Promoting peer to peer learning, creativity and experimentation

Abstract: The importance of integrating technology into the classroom has become a priority at most levels of the curriculum in many countries around the world. This paper draws on the evaluation and research that informed four outreach programs. The authors acknowledge that teachers are generally time poor and often have limited information and communication technology (ICT) skills and confidence, while students have skills and knowledge in ICT that often go untapped in the classroom. They present a curriculum that pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The concept of e-learning within the field of andragogy is based on the ideas of a specific social and cultural phenomenon and those organizational and pedagogical principles that underlie the education systems [6,19,23]. It is necessary to provide the person with opportunities to solve the problems facing the society:…”
Section: Methodsmentioning
confidence: 99%
“…The concept of e-learning within the field of andragogy is based on the ideas of a specific social and cultural phenomenon and those organizational and pedagogical principles that underlie the education systems [6,19,23]. It is necessary to provide the person with opportunities to solve the problems facing the society:…”
Section: Methodsmentioning
confidence: 99%
“…While the benefits of peer and social learning have been well-established and widely accepted, methods for their effective facilitation among large communities of diverse learners still remains a challenge (Chiu & Hew, 2018;Potts et al, 2018). Previous research has explored the impact of using technology to promote peer-learning in many contexts including computer conferencing and learner communities (Wise & Cui, 2018;Zhao et al, 2014), recommender systems (George & Lai, 2019;Zheng & Yano, 2007), and as a mechanism to utilise students' untapped information, communication technology (ICT) skills while building student-led learning practices (Lang et al, 2017). In this study, we focused on exploring the impact of using technology to promote peer learning in the form of partnering with students as co-creators of content.…”
Section: Background On Peer Learning and Student Co-created Contentmentioning
confidence: 99%
“…Our understanding is that there is much potential in peer learning -much more than what we currently use. Pupils could be used more in teaching, i.e., peer-to-peer learning, which, according to Lang et al (2017Lang et al ( , p. 1492, 'can provide relevance and support to both teachers and peers and can be extended to a pedagogy of outreach that includes preservice teachers, IT teachers and their peers'. However, this also requires teachers to be able to change their ideology of what their role is: they need to be able to step aside and make room for the pupils to be the experts, as they might possess more knowledge about some issues than the teacher.…”
Section: Pedagogical Implicationsmentioning
confidence: 99%
“…This can take pressure off teachers, who have to continually adapt to and adopt new knowledge and methods, and whose workload is already heavy as it is. The idea of using students as peer-teachers is not exceptional (e.g., Lang et al, 2017). Sullivan et al (2015) reported the experiences of students teaching other students in ICT skills.…”
Section: Pedagogical Implicationsmentioning
confidence: 99%